Sacroplasty versus Vertebroplasty: Comparable Clinical Outcomes for the Treatment of Fracture-Related Pain - Whitlow, C.T. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Little is known about the long-term clinical outcomes of sacroplasty, a relatively new minimally invasive percutaneous procedure for the treatment of sacral insufficiency fractures. The first purpose of the present study, therefore, was to investigate the effects of sacroplasty on pain, mobility, and activities of daily living (ADLs). A second purpose was to compare clinical outcomes of sacroplasty with those of vertebroplasty, a similar but more established procedure. MATERIALS AND METHODS: A retrospective case series of 12 patients who had a sacroplasty and a control group of 21 patients who had undergone a vertebroplasty was conducted. A 12-item questionnaire and subsequent telephone interview requested each patient to rate the intensity of pain, as well as the ability to ambulate and perform ADLs, before sacroplasty or vertebroplasty, and at the time of the interview. RESULTS: There was a statistically significant decrease in overall self-reported pain, as well as an increase in self-reported ability to ambulate and perform ADLs after sacroplasty or vertebroplasty. These improvements were equivalent, regardless of which procedure the patient received. CONCLUSION: The present study suggests that the treatment of sacral insufficiency fractures with sacroplasty produces relatively long-lasting improvements in pain, mobility, and the ability to perform ADLs. These data also suggest that the clinical outcomes of sacroplasty are comparable with those of vertebroplasty, an accepted and more routinely performed procedure.